Knowledge, Attitude, and Practices Towards Preventive Strategies Against COVID-19 Pandemic Among Nigerian Young Adults: A Cross-Sectional Survey - Odeyemi, Olubunmi; Eyitayo, James; Ogunfolaji, Oloruntoba; Williams, Shekinah; Akande, Michael; Akinola, Onaopemipo (International Journal of Medical Students, 2022)
Background: Since the onset of the COVID-19 pandemic, efforts have been aimed at promoting preventive measures towards curtailing the spread of the SARS-CoV-2 virus. The effectiveness of measures put in place by the government are mostly determined by the Knowledge, Attitude, and Practices (KAP) of the citizenry. We sought to determine the KAP of young Nigerian adults towards preventive strategies against COVID-19. Methods: An online survey was prepared using an 18-question questionnaire to assess the KAP of each participant that satisfied predefined criteria. Data obtained were screened for error and analyzed with SPSS version 23. The level of significance was set at p<0.05. Results: A total of 925 valid responses were received with a 96.25% response rate. Females made up 52.4% of the respondents, 62.4% were aged between 21-24, and 88.4% were from South-western Nigeria. The mean knowledge score was 9.02 (SD 1.18) with a maximum possible knowledge score of 13. Most of the participants (91.7%) agreed that COVID-19 will eventually be successfully controlled. Only 31.1% however had been wearing masks when leaving home. The confidence of winning the battle against COVID-19 differed significantly across the ethnic groups (p<0.01). Ages between 15 and 24 were more likely to visit crowded places (p<0.01). Conclusion: This study revealed a good knowledge level and an optimistic attitude towards the control of the COVID-19 pandemic. However, much more work is needed by government and health officials to translate these to better practices towards prevention and control as the fight against the COVID-19 pandemic continues.